The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1063/1.1814632
|View full text |Cite
|
Sign up to set email alerts
|

Damage induced by low-energy electrons in solid films of tetrahydrofuran

Abstract: We report on the low-energy electron-induced production of aldehydes within thin solid films of tetrahydrofuran (THF) condensed on a solid Kr substrate. The aldehyde fragments, which remain trapped within the bulk of the THF film, are detected in situ via their 3,1(n-->pi*) and 3(pi-->pi*) electronic transitions and vibrational excitations in the ground state using high-resolution electron-energy-loss spectroscopy. The production of aldehyde is studied as a function of the electron exposure, film thickness, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 46 publications
1
42
1
Order By: Relevance
“…Antic et al 3 reported a resonance at 23 eV which decayed into a highly excited state undergoing a further dipolar dissociation. The formation of aldehydes from THF frozen on a Kr substrate was studied in detail by Breton et al 4 and Ja¨ggle et al 5 by means of vibrational and electronic EELS of the products. A strong rise of aldehyde production was observed from about 6 eV upward and was correlated to (n,s * CO ) electronic excitation threshold of THF, together with core-excited resonances around 9 and 10 eV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antic et al 3 reported a resonance at 23 eV which decayed into a highly excited state undergoing a further dipolar dissociation. The formation of aldehydes from THF frozen on a Kr substrate was studied in detail by Breton et al 4 and Ja¨ggle et al 5 by means of vibrational and electronic EELS of the products. A strong rise of aldehyde production was observed from about 6 eV upward and was correlated to (n,s * CO ) electronic excitation threshold of THF, together with core-excited resonances around 9 and 10 eV.…”
Section: Introductionmentioning
confidence: 99%
“…We presume that the C-O bond does break in THF, but the resulting CH 2 (CH 2 ) 3 O À ion is metastable in respect to autodetachment, which would in this case require that the ring is re-closed. The initial CH 2 (CH 2 ) 3 O À ion could be stabilized in the condensed phase, however, and give rise to the weak process reported around 3 eV by Breton et al 4 …”
mentioning
confidence: 95%
“…Antic et al [5] reported a resonance at 23 eV which decays into a highly excited state undergoing a further dipolar dissociation. The formation of aldehydes from THF frozen on a Kr substrate was studied in detail by Breton et al [6] and Jäggle et al [7] by means of vibrational and electronic EELS of the products. Strong rise of aldehyde production was observed from about 6 eV and correlated to (n, σ * CO ) electronic excitation threshold of THF, together with core-excited resonances around 9 and 10 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Condensedphase experiments on thymidine and a single-strand oligonucleotide have demonstrated that slow electrons do indeed break the C-O phosphate-sugar bonds as well as the C-N base-sugar bonds, [60][61][62] and C-O bond breaking was also found in gas-phase DA to a model phosphodiester. 63 A few electron-collision studies, experimental and theoretical, have looked at the individual backbone constituents, i.e., ribose or deoxyribose and a phosphate group, [64][65][66][67][68][69] and others have also been made of electron collisions with backbone analogs such as tetrahydrofuran, 29,65,[68][69][70][71][72][73][74][75][76][77][78][79] tetrahydrofurfuryl alcohol, 71,72,80,81 fructose, 79 and dibutyl phosphate. 63 However, the only electron collision measurements involving nucleosides that we are aware of are the study by Zheng et al of thymine desorption from condensed-phase deoxythymidine 60 mentioned earlier, and the gas-phase studies by Abdoul-Carime et al 82 and by Denifl et al 83 of DA to deoxythymidine and 5-bromouridine, respectively.…”
Section: Introductionmentioning
confidence: 99%